Egghead and brainiac are essential for glycosphingolipid biosynthesis in vivo. - Wandall, H.H.; Pizette, S.; Pedersen, J.W.; Eichert, H.; Levery, S.B.; Mandel, U.; Cohen, S.M.; Clausen, H. (Journal of Biological Chemistry, 2005)
The Drosophila genes, brainiac and egghead, encode glycosyltransferases predicted to act sequentially in early steps of glycosphingolipid biosynthesis, and both genes are required for development in Drosophila. egghead encodes a beta4-mannosyltransferase, and brainiac encodes a beta3-N-acetylglucosaminyltransferase predicted by in vitro analysis to control synthesis of the glycosphingolipid core structure, GlcNAcbeta1-3Manbeta1-4Glcbeta1-Cer, found widely in invertebrates but not vertebrates. In this report we present direct in vivo evidence for this hypothesis. egghead and brainiac mutants lack elongated glycosphingolipids and exhibit accumulation of the truncated precursor glycosphingolipids. Furthermore, we demonstrate that despite fundamental differences in the core structure of mammalian and Drosophila glycosphingolipids, the Drosophila egghead mutant can be rescued by introduction of the mammalian lactosylceramide glycosphingolipid biosynthetic pathway (Galbeta1-4Glcbeta1-Cer) using a human beta4-galactosyltransferase (beta4Gal-T6) transgene. Conversely, introduction of egghead in vertebrate cells (Chinese hamster ovary) resulted in near complete blockage of biosynthesis of glycosphingolipids and accumulation of Manbeta1-4Glcbeta1-Cer. The study demonstrates that glycosphingolipids are essential for development of complex organisms and suggests that the function of the Drosophila glycosphingolipids in development does not depend on the core structure.